Editorial The Techno-Sustainable Alliance: A Call for Solutions - Sonali Bhattacharya; Dipasha Sharma (Australasian Accounting, Business and Finance Journal, 2025)
We are navigating a turbulent, uncertain, novel, and ambiguous (TUNA) business environment. The evolving geopolitical landscape, the severe consequences of climate change, and rapid technological advancements are contributing to diverse socio-economic conditions across the globe. As a result, the field of management must continually reinvent itself to keep pace with these dynamic changes. It has transitioned from being merely multidisciplinary and interdisciplinary to embracing a transdisciplinary approach. Today’s managers must collaborate not only with internal stakeholders such as employees, customers, and shareholders but also with external actors like gender specialists, scientists, activists, reformers, and others.
Keywords: Editorial; Special Issue; Techno-Sustainable Alliance; India; TUNA; Management